Telomeric Repeat-Binding Factor Homologs in Entamoeba histolytica: New Clues for Telomeric Research - Rendón-Gandarilla, Francisco Javier; Álvarez-Hernández, Víctor; Castañeda-Ortiz, Elizabeth J.; Cárdenas-Hernández, Helios; Cárdenas-Guerra, Rosa Elena; Valdés, Jesús; Betanzos, Abigail; Chávez-Munguía, Bibiana; Lagunes-Guillen, Anel; Orozco, Esther; López-Canovas, Lilia; Azuara-Liceaga, Elisa (Frontiers in Cellular and Infection Microbiology, 2018)
Telomeric Repeat Binding Factors (TRFs) are architectural nuclear proteins with critical roles in telomere-length regulation, chromosome end protection and, fusion prevention, DNA damage detection, and senescence regulation. Entamoeba histolytica, the parasite responsible of human amoebiasis, harbors three homologs of human TRFs, based on sequence similarities to their Myb DNA binding domain. These proteins were dubbed EhTRF-like I, II and III. In this work, we revealed that EhTRF-like I and II share similarity with human TRF1, while EhTRF-like III shares similarity with human TRF2 by in silico approach. The analysis of ehtrf-like genes showed they are expressed differentially under basal culture conditions. We also studied the cellular localization of EhTRF-like I and III proteins using subcellular fractionation and western blot assays. EhTRF-like I and III proteins were enriched in the nuclear fraction, but they were also present in the cytoplasm. Indirect immunofluorescence showed that these proteins were located at the nuclear periphery co-localizing with Lamin B1 and trimethylated H4K20, which is a characteristic mark of heterochromatic regions and telomeres. We found by transmission electron microscopy that EhTRF-like III was located in regions of more condensed chromatin. Finally, EMSA assays showed that EhTRF-like III forms specific DNA-protein complexes with telomeric related sequences. Our data suggested that EhTRF-like proteins play a role in the maintenance of the chromosome ends in this parasite.